Lithium ion battery electrode pre-coated with interfacial film as well as preparation method and application of lithium ion battery electrode
By pre-covering the surface of the lithium-ion battery electrode material using liquid phase method to form an artificial interface film, the problem of lithium ions consumption in the formation of SEI film is solved, and the circulation performance and applicability of the battery are improved.
Patent Information
- Application Number
- CN202411969637.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, the formation of the SEI film consumes lithium ions, resulting in irreversible capacity loss during the first charge and discharge process, and reducing the initial charge and discharge efficiency of the battery.
The liquid phase method is used to pre-cover the surface of the electrode material to form an artificial interface film. By selecting appropriate film forming agents such as boric acid, phosphoric acid, etc., a stable interface film is formed to reduce the consumption of lithium ions.
It effectively reduces the consumption of lithium ions, improves the circulation performance of the battery, and this method hardly increases processing steps, making it suitable for industrial applications.
Smart Images

Figure CN119905588A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium ion battery electrode pre-coated with an interface film, and a preparation method and application thereof. Background Art
[0002] The rapid development of commercial lithium-ion batteries is closely related to the progress of electrode materials. At present, the processing of electrode materials tends to be more and more refined. The methods of improving the performance of materials such as secondary sintering, tertiary sintering, coating, and doping modification are all common material manufacturing processes. Although the processing technology of electrode materials is becoming more and more refined, stabilizing the internal structure of the material and improving the surface state, it is difficult to form an ideal interface film because this improvement is carried out at high temperature (above 300°C).
[0003] During the first charge and discharge process of liquid lithium-ion batteries, a passivation layer will form at the solid-liquid interface between the electrode material and the electrolyte. This passivation layer with solid electrolyte characteristics is called the solid electrolyte interface film (SEI film). The SEI film is an insulator for electrons, but it is not very effective for Li + It is a good conductor, allowing Li + Freely embed and remove. The existence of SEI film is crucial to battery performance. First, SEI film can prevent solvent molecules from being co-embedded in electrode materials, thereby protecting the structure of electrode materials from being destroyed and significantly improving the cycle performance and service life of the electrode; secondly, SEI film can maintain the stability and safety of the battery and prevent overly intense chemical reactions from occurring inside the battery.
[0004] However, the formation of SEI film will consume lithium ions, resulting in irreversible capacity loss during the first charge and discharge process, reducing the initial charge and discharge efficiency of the battery. Summary of the invention
[0005] The present invention aims to overcome the problem in the prior art that the formation of the SEI film consumes lithium ions, resulting in irreversible capacity loss during the first charge and discharge process, and reducing the initial charge and discharge efficiency of the battery. The present invention provides a lithium ion battery electrode pre-coated with an interface film, and a preparation method and application thereof. The liquid phase method is used to pre-coat the surface of the electrode material to form an artificial interface film. The artificial interface film can exist stably during the charge and discharge process, effectively reducing the consumption of lithium ions and improving the cycle performance of the battery. Moreover, the process of forming the artificial interface film of the present invention can hardly increase the processing steps, and is suitable for industrial application.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a lithium ion battery electrode pre-coated with an interface film, comprising the following steps: (1) dissolving a film-forming agent and a binder in a solvent, then adding an electrode material and a conductive agent, and dispersing them uniformly to obtain a slurry; the film-forming agent is selected from one or more of boric acid, metaboric acid, tetrafluoroboric acid, nitric acid, phosphoric acid, polyphosphoric acid, metaphosphoric acid, oxalic acid, lithium borate, lithium metaborate, lithium tetraborate, lithium nitrate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium metaphosphate, lithium carbonate, lithium oxalate, and lithium hydrogen oxalate; (2) The slurry is coated on a current collector and dried to obtain a lithium-ion battery electrode pre-coated with the interface film.
[0007] The present invention utilizes the strong solubility of the solvent in the slurry mixing process, dissolves the film-forming agent in the solvent, and then adds the electrode material for dispersion. At this time, since the film-forming agent is in a dissolved state and the electrode material is in a dispersed state (insoluble), the film-forming agent can be evenly distributed on the surface of the electrode material, and the coating is completed in the subsequent drying (solvent removal) process, thereby achieving almost no additional processing steps, and an artificial interface film can be formed on the surface of the electrode material, which is suitable for industrial production. The interface film formed by the liquid phase method of the present invention has good uniformity and adjustable composition. By selecting the type of film-forming agent, a stable artificial interface film can be formed on the surface of the electrode material, which can stably exist during the charge and discharge process, effectively reducing the consumption of lithium ions and improving the cycle performance of the battery.
[0008] Preferably, the mass of the added film-forming agent is 0.05-5% of the mass of the electrode material. If the amount of the film-forming agent is too little, the electrode material will not be completely coated; if the amount of the film-forming agent is too much, the interface film formed on the electrode surface will be too thick, which is not conducive to lithium ion transmission.
[0009] Preferably, the electrode material is a lithium-containing oxide or a carbon-based electrode material; The lithium-containing oxide is selected from one or more of lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium nickel manganese oxide, lithium titanate, lithium iron phosphate, lithium iron manganese phosphate, and lithium-rich manganese-based materials; The carbon-based electrode material is selected from one or more of natural graphite, artificial graphite, modified coated graphite, hard carbon and soft carbon.
[0010] Preferably, when the electrode material is a negative electrode material, the film-forming agent includes boric acid and phosphoric acid in a mass ratio of 25:30-40; when the electrode material is a positive electrode material, the film-forming agent is oxalic acid. The present invention selects different types of film-forming agents to match different electrode materials, which can improve the quality of the formed interface film, make it more stable, have better lithium ion conductivity, and improve the cycle performance of the battery.
[0011] Preferably, when the electrode material is a lithium-containing oxide, the solvent is an amide solvent; when the electrode material is a carbon-based electrode material, the solvent is at least one of an amide solvent and water.
[0012] Preferably, the amide solvent is selected from at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide and N,N-diethylformamide.
[0013] Preferably, the binder is one or more of PVDF, CMC, and SBR emulsion; the mass ratio of the binder to the electrode material is 1:10-50.
[0014] Preferably, the conductive agent is selected from at least one of carbon black, carbon nanotubes, graphene, and conductive graphite; and the mass ratio of the conductive agent to the electrode material is 1:60-100.
[0015] In a second aspect, the present invention provides a lithium ion battery electrode pre-coated with an interface film prepared using the above preparation method.
[0016] In a third aspect, the present invention provides an application of a lithium ion battery electrode pre-coated with an interface film prepared by the above preparation method in a lithium ion battery, wherein the voltage range of a single cell of the lithium ion battery is between 1.5 and 4.9V.
[0017] Therefore, the present invention has the following beneficial effects: (1) The artificial interface film is coated on the surface of the electrode material by the liquid phase method. The interface film has good uniformity and adjustable composition, and can be realized without adding processing steps, which is suitable for industrial production; (2) By selecting the type of film-forming agent, a stable artificial interface film can be formed on the surface of the electrode material, which can exist stably during the charge and discharge process, effectively reducing the consumption of lithium ions and improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a comparison diagram of the SOC-DCR curves of the lithium titanate batteries in the discharge state in Example 1 of the present invention and in Comparative Example 1.
[0019] Figure 2 It is a comparison diagram of the SOC-DCR curves of the charging states of the lithium titanate batteries in Example 1 of the present invention and Comparative Example 1.
[0020] Figure 3 It is a comparison chart of the 60°C cycle performance of the lithium titanate batteries in Example 1 of the present invention and Comparative Example 1.
[0021] Figure 4 It is a comparison diagram of the SOC-DCR curves of the lithium titanate batteries in the discharge state in Example 2 of the present invention and in Comparative Example 1.
[0022] Figure 5It is a comparison diagram of the SOC-DCR curves of the charging states of the lithium titanate batteries in Example 2 of the present invention and Comparative Example 1.
[0023] Figure 6 It is a comparison chart of the 60°C cycle performance of the lithium titanate batteries in Example 2 of the present invention and Comparative Example 1.
[0024] Figure 7 It is a comparison diagram of the SOC-DCR curves of the ternary lithium battery in the discharge state of Example 3 of the present invention and Comparative Example 2.
[0025] Figure 8 It is a comparison diagram of the SOC-DCR curves of the charging states of the ternary lithium batteries in Example 3 of the present invention and Comparative Example 2.
[0026] Fig. 9 It is a comparison chart of the 45°C cycle performance of the ternary lithium batteries in Example 3 of the present invention and Comparative Example 2.
[0027] Fig.10 It is a comparison diagram of the SOC-DCR curves of the ternary lithium batteries in the discharge state of Example 4 of the present invention and Comparative Example 2.
[0028] Fig.11 It is a comparison diagram of the SOC-DCR curves of the charging states of the ternary lithium batteries in Example 4 of the present invention and Comparative Example 2.
[0029] Fig.12 It is a comparison chart of the 45°C cycle performance of the ternary lithium batteries in Example 4 of the present invention and Comparative Example 2.
[0030] Fig.13 It is a comparison diagram of the SOC-DCR curves of the ternary lithium battery in the discharge state of Example 5 of the present invention and Comparative Example 2.
[0031] Fig.14 It is a comparison diagram of the SOC-DCR curves of the charging states of the ternary lithium batteries in Example 5 of the present invention and Comparative Example 2.
[0032] Fig.15 It is a comparison chart of the 45°C cycle performance of the ternary lithium batteries in Example 5 of the present invention and Comparative Example 2.
[0033] Fig.16 It is a comparison diagram of the SOC-DCR curves of the ternary lithium battery in the discharge state of Example 6 of the present invention and Comparative Example 2.
[0034] Fig.17 It is a comparison diagram of the SOC-DCR curves of the charging states of the ternary lithium batteries in Example 6 of the present invention and Comparative Example 2.
[0035] Fig.18It is a comparison chart of the 45°C cycle performance of the ternary lithium batteries in Example 6 of the present invention and Comparative Example 2.
[0036] Fig.19 It is a comparison diagram of the SOC-DCR curves of the ternary lithium batteries in comparative examples 2 and 3 of the present invention in the discharge state.
[0037] Fig. 20 It is a comparison diagram of the SOC-DCR curves of the charging states of the ternary lithium batteries in Comparative Examples 2 and 3 of the present invention.
[0038] Fig.21 It is a comparison chart of the 45°C cycle performance of the ternary lithium batteries in Comparative Examples 2 and 3 of the present invention.
[0039] Fig. 22 It is a comparison diagram of the SOC-DCR curves of the ternary lithium batteries in comparative examples 4 and 5 of the present invention in the discharge state.
[0040] Fig.23 It is a comparison diagram of the SOC-DCR curves of the charging states of the ternary lithium batteries in Comparative Examples 4 and 5 of the present invention.
[0041] Fig.24 It is a comparison chart of the 45°C cycle performance of the ternary lithium batteries in Comparative Examples 4 and 5 of the present invention.
[0042] Among them, (a) Example 1; (b) Example 2; (c) Example 3; (d) Example 4; (e) Example 5; (f) Example 6; (g) Comparative Example 1; (h) Comparative Example 2; (i) Comparative Example 3; (j) Comparative Example 4; (k) Comparative Example 5. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0044] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0045] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with specific implementation methods, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the claims of the present invention.
[0046] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0047] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0048] Overall embodiment: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) dissolving a film-forming agent and a binder in a solvent, then adding an electrode material and a conductive agent, and dispersing them uniformly to obtain a slurry; the film-forming agent is selected from one or more of boric acid, metaboric acid, tetrafluoroboric acid, nitric acid, phosphoric acid, polyphosphoric acid, metaphosphoric acid, oxalic acid, lithium borate, lithium metaborate, lithium tetraborate, lithium nitrate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium metaphosphate, lithium carbonate, lithium oxalate, and lithium hydrogen oxalate; (2) The slurry is coated on a current collector and dried to obtain a lithium-ion battery electrode pre-coated with the interface film.
[0049] As a specific implementation manner, the mass of the added film-forming agent is 0.05-5% of the mass of the electrode material; preferably, the mass of the added film-forming agent is 0.5-2% of the mass of the electrode material.
[0050] As a specific embodiment, the electrode material is a lithium-containing oxide or a carbon-based electrode material; The lithium-containing oxide is selected from one or more of lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium nickel manganese oxide, lithium titanate, lithium iron phosphate, lithium iron manganese phosphate, and lithium-rich manganese-based materials; The carbon-based electrode material is selected from one or more of natural graphite, artificial graphite, modified coated graphite, hard carbon and soft carbon.
[0051] As a specific implementation, when the electrode material is a negative electrode material, the film-forming agent includes boric acid and phosphoric acid in a mass ratio of 25:30-40; when the electrode material is a positive electrode material, the film-forming agent is oxalic acid.
[0052] As a specific implementation, when the electrode material is a lithium-containing oxide, the solvent is an amide solvent; when the electrode material is a carbon-based electrode material, the solvent is at least one of an amide solvent and water.
[0053] As a specific implementation, the amide solvent is selected from at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide, and N,N-diethylformamide.
[0054] As a specific implementation manner, the mass ratio of the solvent to the electrode material is 1~2:1.
[0055] As a specific implementation manner, the binder is one or more of PVDF, CMC, and SBR emulsion; the mass ratio of the binder to the electrode material is 1:10~50.
[0056] As a specific implementation, the conductive agent is selected from at least one of carbon black, carbon nanotubes, graphene, and conductive graphite; the mass ratio of the conductive agent to the electrode material is 1:60-100.
[0057] As a specific implementation, the current collector in step (2) is aluminum foil or copper foil.
[0058] As a specific embodiment, the coating amount of the electrode material on the current collector in step (2) is 60-380 g / m 2 .
[0059] As a specific implementation, the drying temperature in step (2) is 110-140°C.
[0060] As a specific implementation, during the drying in step (2), at least one of steam, electric heat, and infrared rays is used as a heat source.
[0061] Embodiment 1: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dehumidified environment, 150 g PVDF and 25 g boric acid were first added to 4.8 kg N-methylpyrrolidone and stirred to dissolve, and then 4 kg lithium titanate material and 60 g conductive carbon black were added to obtain a slurry after high-speed dispersion; (2) The above slurry was coated on an aluminum foil with a thickness of 13 μm. The coating amount of lithium titanate material was 200 g / m 2 ; Electric heating and drying at 135° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the negative electrode sheet for the preparation of lithium titanate battery. The positive electrode was nickel-cobalt-manganese ternary material. The electrolyte was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge-discharge DCR-SOC curve and the cycle performance at 60°C were tested in the voltage range of 1.5~2.8V. The results are as follows: Figure 1~Figure 3 as shown in .
[0062] Embodiment 2: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dehumidified environment, 150 g PVDF and 35 g polyphosphoric acid were first added to 4.8 kg N-methylpyrrolidone and stirred to dissolve, and then 4 kg lithium titanate material and 60 g conductive carbon black were added to obtain a slurry after high-speed dispersion; (2) The above slurry was coated on an aluminum foil with a thickness of 13 μm. The coating amount of lithium titanate material was 200 g / m 2 ; Electric heating and drying at 135° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the negative electrode sheet for the preparation of lithium titanate battery. The positive electrode was nickel-cobalt-manganese ternary material. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 60°C were tested in the voltage range of 1.5~2.8V. The results are as follows: Figure 4~Figure 6 as shown in .
[0063] Embodiment 3: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dust removal environment, first add 65g CMC and 40g boric acid into 4kg pure water and stir to dissolve, then add 4kg artificial graphite material, 65g conductive carbon black and 220g SBR emulsion, and obtain slurry after high-speed dispersion; (2) The above slurry was coated on a copper foil with a thickness of 8 μm. The coating amount of artificial graphite material was 98 g / m 2 ; Electric heating and drying at 115° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the negative electrode sheet for the preparation of a ternary lithium battery. The positive electrode was a nickel-cobalt-manganese ternary material. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 45°C were tested in the voltage range of 2.8~4.2V. The results are as follows: Figure 7~Figure 9 as shown in .
[0064] Embodiment 4: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dust removal environment, first add 65g CMC and 56g phosphoric acid into 4kg pure water and stir to dissolve, then add 4kg artificial graphite material, 65g conductive carbon black and 220g SBR emulsion, and obtain slurry after high-speed dispersion; (2) The above slurry was coated on a copper foil with a thickness of 8 μm. The coating amount of artificial graphite material was 98 g / m 2; Electric heating and drying at 115° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the negative electrode sheet for the preparation of a ternary lithium battery. The positive electrode was a nickel-cobalt-manganese ternary material. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 45°C were tested in the voltage range of 2.8~4.2V. The results are as follows: Figure 10~Figure 12 as shown in .
[0065] Embodiment 5: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dust removal environment, first add 65g CMC, 25g boric acid, and 38g phosphoric acid into 4kg pure water and stir to dissolve, then add 4kg artificial graphite material, 65g conductive carbon black, and 220g SBR emulsion, and obtain slurry after high-speed dispersion; (2) The above slurry was coated on a copper foil with a thickness of 8 μm. The coating amount of artificial graphite material was 98 g / m 2 ; Electric heating and drying at 115° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the negative electrode sheet for the preparation of a ternary lithium battery. The positive electrode was a nickel-cobalt-manganese ternary material. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 45°C were tested in the voltage range of 2.8~4.2V. The results are as follows: Figure 13~Figure 15 as shown in .
[0066] Embodiment 6: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dust removal environment, first add 65g CMC, 15g lithium carbonate, and 38g phosphoric acid into 4kg pure water and stir to dissolve, then add 4kg artificial graphite material, 65g conductive carbon black and 220g SBR emulsion, and obtain slurry after high-speed dispersion; (2) The above slurry was coated on a copper foil with a thickness of 8 μm. The coating amount of artificial graphite material was 98 g / m 2 ; Electric heating and drying at 115° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the negative electrode sheet for the preparation of a ternary lithium battery. The positive electrode was a nickel-cobalt-manganese ternary material. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 45°C were tested in the voltage range of 2.8~4.2V. The results are as follows: Figure 16~Figure 18 as shown in .
[0067] Comparative Example 1: A method for preparing a lithium ion battery electrode comprises the following steps: (1) In a dehumidified environment, first add 150g PVDF into 4.8kg N-methylpyrrolidone and stir to dissolve, then add 4kg lithium titanate material and 60g conductive carbon black, and obtain slurry after high-speed dispersion; (2) The above slurry was coated on an aluminum foil with a thickness of 13 μm. The coating amount of lithium titanate material was 200 g / m 2 ; Electric heating and drying at 135° C. to obtain the lithium ion battery electrode; (3) The obtained lithium-ion battery electrode was used as the negative electrode sheet for the preparation of lithium titanate battery. The positive electrode was nickel-cobalt-manganese ternary material. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 60°C were tested in the voltage range of 1.5~2.8V. The results are as follows Figure 1 to Figure 6 as shown in .
[0068] Comparative Example 2: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dust removal environment, first add 65g CMC into 4kg pure water and stir to dissolve, then add 4kg artificial graphite material, 65g conductive carbon black and 220g SBR emulsion, and obtain slurry after high-speed dispersion; (2) The above slurry was coated on a copper foil with a thickness of 8 μm. The coating amount of artificial graphite material was 98 g / m 2 ; Electric heating and drying at 115° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the negative electrode sheet for the preparation of a ternary lithium battery. The positive electrode was a nickel-cobalt-manganese ternary material. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 45°C were tested in the voltage range of 2.8~4.2V. The results are as follows: Figure 7 to Figure 21 as shown in .
[0069] Comparative Example 3: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dehumidified environment, 82 g PVDF and 30 g polyphosphoric acid were first added to 2 kg N-methylpyrrolidone and stirred to dissolve, and then 4 kg nickel cobalt lithium manganese oxide ternary material and 60 g conductive carbon black were added to obtain a slurry after high-speed dispersion; (2) The above slurry was coated on an aluminum foil with a thickness of 13 μm. The coating amount of the nickel-cobalt-lithium-manganese oxide ternary material was 320 g / m 2 ; Electric heating and drying at 125° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the positive electrode for the preparation of a ternary lithium battery. The negative electrode was artificial graphite. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 45°C were tested in the voltage range of 2.8~4.2V. The results are as follows: Figure 19~Figure 21 as shown in .
[0070] Comparative Example 4: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dehumidified environment, 82 g of PVDF and 24 g of oxalic acid were first added to 2 kg of N-methylpyrrolidone and stirred to dissolve, and then 4 kg of nickel cobalt lithium manganese oxide ternary material and 60 g of conductive carbon black were added to obtain a slurry after high-speed dispersion; (2) The above slurry was coated on an aluminum foil with a thickness of 13 μm. The coating amount of the nickel-cobalt-lithium-manganese oxide ternary material was 320 g / m 2 ; Electric heating and drying at 125° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained pre-coated interface film lithium-ion battery electrode was used as the positive electrode for the preparation of lithium titanate battery. The negative electrode was artificial graphite. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 45°C were tested in the voltage range of 2.8~4.2V. The results Figures 22-24 shown.
[0071] Comparative Example 5: A method for preparing a lithium ion battery electrode pre-coated with an interface film comprises the following steps: (1) In a dehumidified environment, 82 g of PVDF was first added to 2 kg of N-methylpyrrolidone and stirred to dissolve, and then 4 kg of nickel cobalt lithium manganese oxide ternary material and 60 g of conductive carbon black were added to obtain a slurry after high-speed dispersion; (2) The above slurry was coated on an aluminum foil with a thickness of 13 μm. The coating amount of the nickel-cobalt-lithium-manganese oxide ternary material was 320 g / m 2 ; Electric heating and drying at 125° C. to obtain the lithium ion battery electrode pre-coated with the interface film; (3) The obtained lithium-ion battery electrode pre-coated with the interface film was used as the positive electrode for the preparation of a ternary lithium battery. The negative electrode was artificial graphite. The electrolyte: solvent was EMC and PC with a volume ratio of 8:2. The concentration of lithium salt LiPF6 was 1 mol / L. The charge and discharge DCR-SOC curve and the cycle performance at 45°C were tested in the voltage range of 2.8~4.2V. The results are as follows: Figure 22~Figure 24 as shown in .
[0072] from Figure 1~Figure 3 From the data comparison between Example 1 and Comparative Example 1, it can be seen that in Example 1, boric acid is coated on the surface of the lithium titanate electrode material by the method of the present invention to form an interface film. Compared with Comparative Example 1 in which the interface film is not coated on the surface of the lithium titanate electrode material, the internal resistance of the battery in the range of SOC of 10% to 90% changes less, and the cycle performance of the battery at 60°C is significantly improved compared with Comparative Example 1.
[0073] from Figure 4~Figure 6 From the data comparison between Example 2 and Comparative Example 1, it can be seen that in Example 2, polyphosphoric acid is used as a film-forming agent to form an interface film on the surface of the lithium titanate electrode material. Compared with Comparative Example 1 without an interface film, the internal resistance of the battery in the SOC range of 10% to 90% changes less, and the cycle performance of the battery at 60°C is also significantly improved.
[0074] from Figure 7~Figure 9 From the data comparison between Example 3 and Comparative Example 2, it can be seen that in Example 3, boric acid is coated on the surface of the artificial graphite electrode material by the method of the present invention to form an interface film. Compared with Comparative Example 2 in which the interface film is not coated on the surface of the artificial graphite material, the internal resistance of the battery in the SOC range of 10% to 90% changes less, and the cycle performance of the battery at 45°C is significantly improved compared with Comparative Example 2.
[0075] from Figure 10~Figure 12 From the data comparison between Example 4 and Comparative Example 2, it can be seen that in Example 4, phosphoric acid is used as a film-forming agent to form an interface film on the surface of the artificial graphite electrode material. Compared with Comparative Example 1 without an interface film, the internal resistance of the battery in the SOC range of 10% to 90% changes less, and the cycle performance of the battery at 45°C is also significantly improved.
[0076] from Figure 13~Figure 15From the data comparison between Example 5 and Comparative Example 2, it can be seen that in Example 5, boric acid and phosphoric acid are used as film-forming agents to form an interface film on the surface of the artificial graphite electrode material. Compared with Comparative Example 2 without coating the interface film, the internal resistance of the battery in the range of SOC of 10% to 90% changes less, and the cycle performance of the battery at 45°C is significantly improved. In addition, in Example 5, boric acid and phosphoric acid are used as film-forming agents, and the cycle performance of the battery is also significantly improved compared with Examples 3 and 4 in which boric acid or phosphoric acid is coated alone.
[0077] from Figure 16~Figure 18 From the data comparison between Example 6 and Comparative Example 2, it can be seen that in Example 6, lithium carbonate and phosphoric acid are used as film-forming agents to form an interface film on the surface of the artificial graphite electrode material. Compared with Comparative Example 2 without an interface film, the internal resistance of the battery changes less in the range of SOC 10% to 90%, and the cycle performance of the battery at 45°C is improved. However, in Example 6, lithium carbonate and phosphoric acid are used as film-forming agents, and the cycle performance of the battery is reduced compared with phosphoric acid alone in Example 4, indicating that the use of appropriate film-forming agents can improve the quality of the formed interface film, make it more stable, have better lithium ion conductivity, and improve the cycle performance of the battery; but if the combination is inappropriate, the film-forming agents will affect each other, which will cause a decrease in the battery cycle performance.
[0078] from Figure 19~Figure 21 From the data comparison between Comparative Example 2 and Comparative Example 3, it can be seen that in Comparative Example 3, polyphosphoric acid is used as a film-forming agent to coat the lithium nickel cobalt manganese oxide positive electrode material. Compared with the coating of the negative electrode material in Comparative Example 2, the internal resistance change of the battery in the SOC range of 10% to 90% is similar, while the cycle performance of the battery at 45°C is reduced.
[0079] from Figure 22~Figure 24 From the data comparison between Comparative Example 4 and Comparative Example 5, it can be seen that in Comparative Example 4, oxalic acid is used to coat the positive electrode material of lithium nickel cobalt manganese oxide. Compared with the case where the positive electrode material of lithium nickel cobalt manganese oxide is not coated in Comparative Example 5, the internal resistance of the battery in the range of SOC of 10% to 90% changes less, and the cycle performance of the battery at 45°C is improved. In addition, in Comparative Example 4, oxalic acid is used as a film-forming agent to coat the positive electrode material of lithium nickel cobalt manganese oxide. Compared with the case where polyphosphoric acid is used as a film-forming agent in Comparative Example 3, the cycle performance of the battery at 45°C is also significantly improved. This shows that not all film-forming schemes have a positive effect. After some interface films are formed, the internal resistance of the battery increases and the cycle deteriorates. This shows that different electrode materials have different matching properties for the components of the interface film. Good matching is beneficial to the electrical performance of the battery, while poor matching is detrimental to the electrical performance of the battery.
[0080] The above content is a further detailed description of the technical solution of the present invention in combination with a specific preferred implementation method, and should not be understood as a limitation on the applicable scope of the present invention. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be deemed to fall within the scope of patent protection determined by the claims submitted for the present invention.
Claims
1. A method for preparing a lithium ion battery electrode pre-coated with an interface film, characterized in that: The steps include: (1) dissolving a film-forming agent and a binder in a solvent, then adding an electrode material and a conductive agent, and dispersing them uniformly to obtain a slurry; the film-forming agent is selected from one or more of boric acid, metaboric acid, tetrafluoroboric acid, nitric acid, phosphoric acid, polyphosphoric acid, metaphosphoric acid, oxalic acid, lithium borate, lithium metaborate, lithium tetraborate, lithium nitrate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium metaphosphate, lithium carbonate, lithium oxalate, and lithium hydrogen oxalate; (2) The slurry is coated on a current collector and dried to obtain a lithium-ion battery electrode pre-coated with the interface film.
2. The method for preparing a lithium ion battery electrode pre-coated with an interface film according to claim 1, characterized in that: The mass of the added film-forming agent is 0.05~5% of the mass of the electrode material.
3. The method for preparing a lithium ion battery electrode pre-coated with an interface film according to claim 1, characterized in that: The electrode material is a lithium-containing oxide or a carbon-based electrode material; The lithium-containing oxide is selected from one or more of lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium nickel manganese oxide, lithium titanate, lithium iron phosphate, lithium iron manganese phosphate, and lithium-rich manganese-based materials; The carbon-based electrode material is selected from one or more of natural graphite, artificial graphite, modified coated graphite, hard carbon and soft carbon.
4. The method for preparing a lithium ion battery electrode pre-coated with an interface film according to claim 3, characterized in that: When the electrode material is a lithium-containing oxide, the solvent is an amide solvent; when the electrode material is a carbon-based electrode material, the solvent is at least one of an amide solvent and water.
5. The method for preparing a lithium ion battery electrode pre-coated with an interface film according to claim 4, characterized in that: The amide solvent is selected from at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide and N,N-diethylformamide.
6. The method for preparing a lithium ion battery electrode pre-coated with an interface film according to claim 1, characterized in that: The binder is one or more of PVDF, CMC and SBR emulsion; the mass ratio of the binder to the electrode material is 1:10-50.
7. The method for preparing a lithium ion battery electrode pre-coated with an interface film according to claim 1, characterized in that: The conductive agent is selected from at least one of carbon black, carbon nanotubes, graphene, and conductive graphite; the mass ratio of the conductive agent to the electrode material is 1:60-100.
8. The method for preparing a lithium ion battery electrode pre-coated with an interface film according to claim 1, characterized in that: In step (2), the coating amount of the electrode material on the current collector is 60~380g / m 2 .
9. A lithium ion battery electrode pre-coated with an interface film, characterized in that: It is prepared using the preparation method described in any one of claims 1 to 8.
10. A lithium ion battery electrode pre-coated with an interface film as claimed in claim 9 or a lithium ion battery electrode pre-coated with an interface film prepared by the preparation method according to any one of claims 1 to 8 in a lithium ion battery, characterized in that: The voltage range of a single cell of the lithium-ion battery is between 1.5V and 4.9V.